Design and Development of a Physics Laboratory Tool Based on Arduino Nano Sensor for the Topic of Uniformly Accelerated Linear Motion (UALM) - Maryani, Maryani; Azizah, Syarifah Y Nur; Febrianty, Wanda; Amri , Hanif Al; Fuadiyah , Tsamratul; Putri , Meylan Kharisma; Subiki, Subiki (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Instructional aids serve as tools used in the teaching process to provide a clearer understanding of concepts and learning materials. The aim of this research is to design, assess the feasibility, and test the accuracy of a physics instructional aid based on Arduino Nano sensor for the topic of Uniformly Accelerated Linear Motion (UALM). The methods used in this research are literature review and design and development. This research consists of two stages: the first stage is the design stage of the instructional aid, and the second stage is the feasibility test of the instructional aid. In the design stage, there are five steps involved: preparing the tools and materials, assembling the track board, assembling the Arduino Nano and distance sensor circuit, assembling the components of the practical apparatus, and evaluation. The feasibility test of the Arduino Nano instructional aid was conducted through two experiments. From the results of the first experiment, testing the feasibility of the Arduino Nano instructional aid for Uniformly Accelerated Linear Motion (UALM), two findings were obtained. In the first experiment, when the time and angle varied, the graph showed that time is inversely proportional to the angle. On the other hand, in the second experiment, when the time and distance varied, the graph indicated that time is directly proportional to the distance.